THE CORRELATION BETWEEN STUDENTS’ SUBJECT-VERB AGREEMENT MASTERY AND THEIR WRITING ABILITY OF DESCRIPTIVE TEXTS - Nurashikin Nurashikin; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research intends to find out whether or not there is a correlation between students’ subject-verb agreement mastery and their writing ability of descriptive texts at SMAN 2 Tapung. There were 56 tenth grade students of social science major chosen as samples. The instruments were subject-verb agreement test and writing descriptive text test. The subject-verb agreement test was used to assess the students’ mastery of subject-verb agreement. The writing descriptive text test was used to assess descriptive text writing ability. The data were obtained by calculating the subject-verb agreement test and writing descriptive text test results. The calculation was done using SPSS Statistics 25. Based on the calculation, it was found that the students’ subject-verb agreement mastery and their descriptive text writing ability are classified into sufficient category. Besides, the value of correlation coefficient obtained was 0.793 which means that there is a correlation between students’ subject-verb agreement mastery and their writing ability of descriptive texts. The correlation is categorized into high correlation since the value of correlation coefficient obtained is 0.793 which is in the range of 0.70 - 0.90. According to determination analysis, subject-verb agreement mastery had a 62.9% influence on the descriptive text writing ability. From the research findings, it is recommended that the English teacher provide more exercises and strategies to help students grasp the rules of subject-verb agreement easily and the students do and practice more exercises on subject-verb agreement. Further, other researchers conduct further research on the correlation between other language skills and language aspects on different sample size and location were also recommended.Key Words: Correlation, Subject-Verb Agreement Mastery, Writing Ability of Descriptive Text